English Training Using Birkenbihl Method to Improve Receptive Skills of Grade VII Students at MTs Putri As'adiyah - Satriani, Satriani; Amiruddin; Razaq, Yusuf (Jurnal Pengabdian Kepada Masyarakat Patikala, 2022)
This program focuses on providing instruction to improve students' receptive abilities through exercises such as decoding text, reading aloud, and filling in the blank for listening using the Birkhenbihl approach during the SLA process. This English camp curriculum yielded four primary outcomes: 1) Male students are better at mastering vocabulary in decoding and active listening activities, 2) female students are better at comprehending the text, 3) age factors have a significant impact on the SLA process, and 4) internal motivation, which is influenced by the student's character, has an impact on the progress of receptive skill improvement. The English camp, which ran from September 7th to October 4th, 2020, was aimed to educate seventh-grade students at Junior High School how to use the Birkhenbihl technique to acquire and improve their English receptive abilities. 133 children, 12 homeroom teachers, 12 tutors, 12 students, 6 lecturers, and parents were influenced by this initiative. The key resource for reading aloud, decoding text, and listening activities is the Birkhenbihl method module. The daily portfolio is a daily portfolio, whereas the weekly portfolio is a weekly portfolio. Character-building exercises also include sunnah or amaliyah activities.